PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK - RIDHO ERICKO (Departemen Matematika, 2018)
Understanding of mathematical concept is one of basic skills that must be developed in according to the purpose of mathemathics learning. However, the reality at school shows that students' understanding of mathematical concepts is still low. Realistic Mathematic Education (RME) approach can be used as a solution. The purpose of this research is to compare students’ understanding of mathematical concepts who learn with RME approach and conventional learning. This type of research is a quasi experiment with static group design. The instruments is tests of understanding of mathematical concepts. Based on data analysis concluded that RME approach gives positive influences to the student’s understanding of mathematical concepts in class VIII SMP Negeri 1 Solok Selatan.Keywords – Understanding of mathematical concept, Realistic Mathematics Education (RME) approach, Conventional Learning